E2 of cottontail rabbit papillomavirus is a nuclear phosphoprotein translated from an mRNA encoding multiple open reading frames. - Barbosa, M S (1988)
The papillomavirus E2 protein is a transcription trans-activator and as such as a paramount effect on viral functions. We have identified and characterized the cottontail rabbit papillomavirus E2 protein expressed from the late simian virus 40 promoter in COS-7 cells. E2 was shown to be a highly phosphorylated 49-kilodalton protein. Subcellular fractionation and indirect immunofluorescent staining indicated that E2 was located in the nuclei. E2 was expressed from a vector which contained just the open reading frame. ORF E2 and also from vectors which extended farther upstream and also expressed E7 or the short E6 protein. However, the level of E2 was very low in cells transfected with a vector expressing the long E6 protein. Mapping of transcripts with nuclease S1 and exonuclease ExoVII in cells expressing the short E6 and E2 proteins showed that E2 was translated from an RNA which encoded the short E6, E7, and E2 proteins but served as mRNA for only the short E6 and E2 proteins.